2021
DOI: 10.1186/s12882-021-02557-x
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19-related acute kidney injury; incidence, risk factors and outcomes in a large UK cohort

Abstract: Background Acute kidney injury (AKI) is common among patients hospitalised with COVID-19 and associated with worse prognosis. The aim of this study was to investigate the epidemiology, risk factors and outcomes of AKI in patients with COVID-19 in a large UK tertiary centre. Methods We analysed data of consecutive adults admitted with a laboratory-confirmed diagnosis of COVID-19 across two sites of a hospital in London, UK, from 1st January to 13th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
2
37
1
8
Order By: Relevance
“…We found that patients with a history of pre-existing CKD were not only at increased risk for developing AKI but also had increased need for RRT overall, and in the second wave, but not in the first wave. These findings were echoed in previous studies as well [ 6 , 20 , 21 , 33 ]. We also found that older patients were less likely to undergo RRT during the first wave but not during the second wave.…”
Section: Discussionsupporting
confidence: 83%
“…We found that patients with a history of pre-existing CKD were not only at increased risk for developing AKI but also had increased need for RRT overall, and in the second wave, but not in the first wave. These findings were echoed in previous studies as well [ 6 , 20 , 21 , 33 ]. We also found that older patients were less likely to undergo RRT during the first wave but not during the second wave.…”
Section: Discussionsupporting
confidence: 83%
“…The lung is considered the primary site of damage in COVID-19 disease, but there are numerous reports that damage also occurs in other organs ( 5 ). In particular, acute tubular injury has been described in the kidney after severe COVID-19 and increase of proteinuria was associated with poor prognosis and increased mortality ( 6 , 7 ). Here, we therefore investigated local complement over-activation as a common pathomechanism in COVID-19-mediated injury in lung and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the kidney is involved in many patients with a considerable proportion of hospitalized patients experiencing primarily acute kidney injury (AKI). In addition, the occurrence of AKI in severe COVID-19 is associated with a higher mortality (6,7). Some studies suggest direct viral infection of glomerular and tubular cells through the ACE2-receptor possibly causing acute proximal tubular injury and detachment of podocytes (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…AKI is common in COVID-19 patients and is associated with a poor prognosis. Some studies have enlightened the role of acute tubular injury and direct renal tropism in the pathophysiology of COVID-19 AKI [ 39 , 40 , 41 , 42 ]. The latter can also explain why AKI is predominant in the Omicron group.…”
Section: Discussionmentioning
confidence: 99%